THE DEVELOPMENT STRATEGY IN MARINE ECO-TOURISM OF NONGSA BEACH BATAM CITY IN RIAU ISLANDS PROVINCE - Tiara Sri Mulawanti; Syafruddin Nasution; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted on May 2016 at Nongsa Beach in Batam City, Riau Islands Province. The purpose of study was to analise the potential of tourism in Nongsa Beach as a marine tourism. The method used in this study is a survey method. The result of the study show that Nongsa Beach has a high potential to serve as a national and international marine ecotourism. This was based on the aspects of chemical physics parameters oceanography, geology and geomorphology, climate coastal ecosystems, historical value, and overview from tour players, and the values of Pengukuran Willingness to Accept (WTA) dan Willlingness to Pay (WTP). The concept of ecotourism can be applied to develop marine tourism in the island based on the analysis of strategy of Strengths – Opportunity (SO), Strategi Weakness - Opportunity (WO), Strategi Strengths – Threats (ST), Strategi Weakness – Threats (WT).Keywords: Nongsa Beach, marine ecotourism, potential and strategies